2017
DOI: 10.3389/fphys.2017.00208
|View full text |Cite
|
Sign up to set email alerts
|

The Variation Tendency of Polyamines Forms and Components of Polyamine Metabolism in Zoysiagrass (Zoysia japonica Steud.) to Salt Stress with Exogenous Spermidine Application

Abstract: To understand dynamic changes in polyamines (PAs) forms and components of polyamine metabolism in zoysiagrass (Zoysia japonica Steud.) response to salt stress with exogenous spermidine (Spd) application, two Chinese zoysia cultivars, z081 and z057, were exposed to sodium chloride stress for 2, 4, 6, and 8 days. The z057 cultivar possesses higher salinity tolerance than the z081 cultivar. Salt stress decreased the zoysiagrass fresh weight (FW) and increased free Spd and spermine (Spm) levels and soluble and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…In this study, the application of exogenous Spd was shown to promote growth and RWC (Table 1) and improve the net photosynthesis in S biotype of E. indica during exposure to salinity (Table 2). This result is consistent with previous findings (Li et al 2017) in which exogenous Spd restored the growth of zoysiagrass under salt stress conditions. Salinity stress increases the production and accumulation of ROS (Parida & Das 2005).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, the application of exogenous Spd was shown to promote growth and RWC (Table 1) and improve the net photosynthesis in S biotype of E. indica during exposure to salinity (Table 2). This result is consistent with previous findings (Li et al 2017) in which exogenous Spd restored the growth of zoysiagrass under salt stress conditions. Salinity stress increases the production and accumulation of ROS (Parida & Das 2005).…”
Section: Discussionsupporting
confidence: 94%
“…This result is consistent with previous findings (Li et al . ) in which exogenous Spd restored the growth of zoysiagrass under salt stress conditions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, metabolic profiling of AD brains revealed that there was significant decline in PA concentrations, revealing another aspect of PAs [ 149 , 150 ]. Studies have shown that age-related region-specific decline of PAs in the cerebral cortex is increased by trauma, this directly suggests that PA system dysregulation may contribute to age-related impairments [ 122 , 150 , 151 , 152 , 153 , 154 ]. Moreover, in the serum of AD patients, it was seen that acetylated spermine, a derivative of spermidine, was downregulated [ 155 , 156 , 157 ].…”
Section: Glial-oriented Potential Therapeutic Targets Of Interestmentioning
confidence: 99%